PERBEDAAN NILAI KONSENTRASI PARAMETER SO2, NO2 DAN PARTIKULAT PM10 (PARTIKEL - Muhammad Zulmi (FT-USNI, 2022)
This study was intended to determine the significance of changes in the concentration of SO2, NO2, and PM10 (particles <10 m) parameters in the free air on Car Free Day before the Pandemic Period and during the Pandemic Period, because the ambient air sampling point was carried out on Car Free Day during the time of the pandemic. This pandemic period is still the same as the period before the 2019 pandemic, namely in the Central Jakarta area around the highway health road area. The methodology used is to carry out direct measurements using an impinger tool to measure SO2 and NO2, and an HVAS tool to measure PM10 (particles <10 m). The time of the study was carried out in April - June 2021, where for data sampling, sampling would be carried out 2 times in one month between the second and third week of each month. The results of the study indicate that Car Free Day during the Pandemic period affects the decrease in pollutant concentration values for SO., NO., and PM10 parameters, where for the PM10 parameter it drops statistically significantly, and for SO., and NO. parameters it does not cause a statistically significant decrease. , where the data analysis was carried out by using the Paired T test with free samples at a significance of = 5%.